Detection of cutaneous leishmaniasis in three communities of Oti Region, Ghana. - Richard Akuffo; Carmen Sanchez; Carmen Chicharro; Eugenia Carrillo; Naiki Attram; Mba-Tihssommah Mosore; Clara Yeboah; Nana Konama Kotey; Daniel Boakye; Jose-Antonio Ruiz-Postigo; Javier Moreno; Michael Wilson; et al. (PLoS Neglected Tropical Diseases)
Background Cutaneous leishmaniasis (CL) is the most common type of leishmaniasis, a neglected tropical disease caused by parasites of the genus Leishmania. In Ghana, some studies in the Volta region have detected Leishmania parasites among persons with skin ulcers. Methodology/principal findings Using a cross-sectional study design, the prevalence of CL in three communities of the Oti Region of Ghana was investigated. Demographic and epidemiological data were obtained by a structured interviewer administered questionnaire. A total of 426 (12.4%) out of 3,440 participants screened had at least one skin ulcer. Of 595 skin ulcers sampled and tested by PCR for Leishmania infection, 150 (25.2%) ulcers from 136 individuals tested positive, accounting for an overall CL prevalence of 31.9% among persons with skin ulcers. Individual community CL prevalence of 23.2%, 29.8%, and 36.8% was observed in Ashiabre, Keri, and Sibi Hilltop respectively among persons with skin ulcers. Conclusions/significance Confirmation of CL in the study area suggests an active cycle of transmission of Leishmania infection. The observation of skin ulcers which tested negative to Leishmania infection suggests a need to test for additional causes of skin ulcers such as Treponema pallidum pertenue and Mycobacterium ulcerans in the study area.